An Analysis of the Effects on Application of Management Accounting Information Systems and Quality Management Accounting Information - Astuty, Widia (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The study aims to prove empirically; (i) the influence of the business environment for the application of management accounting information systems; (ii) the influence of ethics on the application of management accounting information systems; (iii) the influence of organizational culture on the implementation of management accounting information systems; and (iv) the effect of the application of motivation of this study due to a phenomenon of having an integration on management accounting information system whereby the information generated is not qualified, as well as the uncertainty of business environment, ethics and organizational culture which are yet to have optimal conditions. The method used is explanatory research with a survey approach, using a statistical tool of SEM Partial Linear Regression, with the aim to obtain facts concerning the occurance of phenomena, seek actual and systematic information on the application of management accounting information systems, and the environment, ethics, organizational culture affect the application of accounting information management system; and the application of management accounting information system affects the quality of information management accounting. Keywords : Business Environment, Ethics. Organizational Culture, Application of Management Accounting Information System, Quality of Information Management Accounting